ANALISIS TEKS: KOHESI DAN KOHERENSI, UNSUR-UNSUR GRAMATIKAL SERTA IMPLIKATUR OPINI DI SURAT KABAR KOMPAS EDISI RABU, 27 MEI 2026 - Doni Uji Windiatmoko (Indonesian language and literature education program Majapahit Islamic University, 2026)
The purpose of this study is to determine the cohesion and coherence, grammatical elements, and implicature in the opinion of